2012
DOI: 10.3389/fimmu.2012.00280
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell Contribution to Human Follicular Lymphoma Pathogenesis

Abstract: Follicular lymphoma (FL) is the prototypical model of indolent B cell lymphoma displaying a strong dependence on a specialized cell microenvironment mimicking normal germinal center. Within malignant cell niches in invaded lymph nodes and bone marrow, external stimuli provided by infiltrating stromal cells make a pivotal contribution to disease development, progression, and drug resistance. The crosstalk between FL B cells and stromal cells is bidirectional, causing activation of both partners. In agreement, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 63 publications
(74 reference statements)
1
49
0
Order By: Relevance
“…2,[27][28][29] However, these parameters do not address the underlying microenvironment and bi-directional crosstalk between FL B-cells and stromal cells that may herald aggressive disease biology in advance of clinical presentation and deterioration. 30 Cytokines present within the tumor microenvironment appear to contribute to growth and survival of malignant cells and also ensures a continued inflammatory milieu recruiting reactive cells to lymphoma tissue. [31][32][33] Elevations in various cytokines have been reported as markers of aggressive lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…2,[27][28][29] However, these parameters do not address the underlying microenvironment and bi-directional crosstalk between FL B-cells and stromal cells that may herald aggressive disease biology in advance of clinical presentation and deterioration. 30 Cytokines present within the tumor microenvironment appear to contribute to growth and survival of malignant cells and also ensures a continued inflammatory milieu recruiting reactive cells to lymphoma tissue. [31][32][33] Elevations in various cytokines have been reported as markers of aggressive lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Further support for the hypothesis that indolent and aggressive lymphoma progression is also determined by the cellular microenvironment, in addition to genomic aberrations of the malignant cells 11,12 , is derived from gene expression profiling in diffuse large B-cell lymphomas. It has been shown that survival of these patients is strongly influenced by immune cell infiltration, fibrosis and angiogenesis, collectively grouped as stromal-1 and -2 signatures 13 .…”
mentioning
confidence: 97%
“…This could result from their cognate nature and ability to encounter antigen-laden FDCs. The preferred tumor cell localization in the FDC-rich GC light zone may also be due to the paracrine provision of growth-promoting factors ( 34,35 ). BCR engagement, as evidenced by activated BTK, and the receipt of growth factors could act differentially during tumor ontogeny and in a complementary manner.…”
Section: Research Articlementioning
confidence: 99%
“…4H ). Next, we mimicked cytokine and growth factor conditions that were suggested to support either GC B-cell proliferation or follicular B-cell lymphoma expansion ( 34,35 ). When supplemented, a substantial increase in cell proliferation was obtained for BAFF, CXCL12, Sonic hedgehog (SHH), hepatocyte growth factor (HGF), CXCL13, and IL15 ( Fig.…”
Section: Research Articlementioning
confidence: 99%